2013
DOI: 10.1371/journal.pone.0061213
|View full text |Cite
|
Sign up to set email alerts
|

CD109 Plays a Role in Osteoclastogenesis

Abstract: Osteoclasts are large multinucleated cells that arise from the fusion of cells from the monocyte/macrophage lineage. Osteoclastogenesis is mediated by macrophage colony-stimulating factor (M-CSF) and receptor activator of nuclear factor-kB ligand (RANKL) and involves a complex multistep process that requires numerous other elements, many of which remain undefined. The primary aim of this project was to identify novel factors which regulate osteoclastogenesis. To carry out this investigation, microarray analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 53 publications
3
22
2
1
Order By: Relevance
“…Additionally, dynamic histomorphometric analysis showed enhanced bone formation in CD109 −/− mice. Additionally, we unexpectedly found that osteoclasts in CD109 −/− bones were large, multinucleated cells that seemingly matured in vivo; this is in contrast to a previous report that osteoclast formation decreases in RAW264.7 cells in vitro when CD109 is suppressed (Wang et al, 2013). This difference in p-values between ES/BS and OV/BV might suggest that bone erosion exceeds osteoid formation in CD109 −/− mice.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Additionally, dynamic histomorphometric analysis showed enhanced bone formation in CD109 −/− mice. Additionally, we unexpectedly found that osteoclasts in CD109 −/− bones were large, multinucleated cells that seemingly matured in vivo; this is in contrast to a previous report that osteoclast formation decreases in RAW264.7 cells in vitro when CD109 is suppressed (Wang et al, 2013). This difference in p-values between ES/BS and OV/BV might suggest that bone erosion exceeds osteoid formation in CD109 −/− mice.…”
Section: Discussioncontrasting
confidence: 90%
“…vitro decreased following CD109 suppression (Wang et al, 2013). We also carried out an osteoclast formation assay, as described in the Supporting Information Appendix S1, and observed reduced osteoclast formation in vitro in primary monocytes from bone marrow of CD109 −/− mice compared with those from CD109 +/+ bone marrow (Figure 3c).…”
Section: Cd109 Was Expressed In Osteoblasts and Osteoclasts In Bonementioning
confidence: 91%
“…It is thought that direct and indirect disturbances in TGF-b signaling may be implicated in the pathologies that associate CD109 with diseased growths [82]. In addition, CD109 has been implicated in the signaling pathway involved in differentiation of osteoclasts from progenitor cell lines [83].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CD109 regulates TGF-β receptor endocytosis and degradation to inhibit TGF-β signaling. Some studies have shown that human cells overexpressing CD109 exhibit enhanced proliferation compared with control cells, so this molecule is known to be involved in tumorigenesis [15,16].…”
Section: Discussionmentioning
confidence: 99%